Antioxidant and Potentially Anti-Inflammatory Activity of Anthocyanin Fractions from Pomace Obtained from Enzymatically Treated Raspberries - Urszula Szymanowska; Barbara Baraniak (MDPI AG, 2019)
Raspberry pomace was obtained from raspberries subjected to enzymatic maceration using three commercial pectinolytic preparations (Pectinex Ultra SP-L, Pectinex Yield Mash, and Ultrazym AFP-L). Phenolic compounds were extracted and anthocyanin fractions were isolated using the SPE solid phase extraction technique. In the separated anthocyanin fractions, the content of individual compounds was determined by the HPLC technique and the antioxidant activity was assessed with four complementary methods (DPPH and ABTS radical scavenging activity, chelating Fe(II) power, and ferric reducing power). Potential anti-inflammatory properties were also identified as the ability to inhibit the activity of lipoxygenase and cyclooxygenase 2. For these enzymes, the type of inhibition was determined based on the Lineweaver−Burke plot.